2020
DOI: 10.1002/cncy.22272
|View full text |Cite
|
Sign up to set email alerts
|

Ki‐67 proliferation index in neuroendocrine tumors: Can augmented reality microscopy with image analysis improve scoring?

Abstract: BackgroundThe Ki‐67 index is important for grading neuroendocrine tumors (NETs) in cytology. However, different counting methods exist. Recently, augmented reality microscopy (ARM) has enabled real‐time image analysis using glass slides. The objective of the current study was to compare different traditional Ki‐67 scoring methods in cell block material with newer methods such as ARM.MethodsKi‐67 immunostained slides from 50 NETs of varying grades were retrieved (39 from the pancreas and 11 metastases). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…13,34,35 For breast cancers, there is a debate about whether the manual analysis of Ki67 should be the gold standard since several studies have shown superior prognostic information from DIA. 39,40 In conclusion, standardized DIA Ki67 scoring gave similar results as subjective scoring but may be a time-saving supplementary tool in surgical pathology 29 that can improve the poor intraobserver and interobserver reliability with manual evaluation methods. 41 DIA PHH3 do not agree so well with routine grading and is not recommended as an alternative to MAI or Ki67 in routine practice.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…13,34,35 For breast cancers, there is a debate about whether the manual analysis of Ki67 should be the gold standard since several studies have shown superior prognostic information from DIA. 39,40 In conclusion, standardized DIA Ki67 scoring gave similar results as subjective scoring but may be a time-saving supplementary tool in surgical pathology 29 that can improve the poor intraobserver and interobserver reliability with manual evaluation methods. 41 DIA PHH3 do not agree so well with routine grading and is not recommended as an alternative to MAI or Ki67 in routine practice.…”
Section: Discussionmentioning
confidence: 71%
“…This study confirms an excellent agreement between the DIA Ki67 and the pathology Ki67, a finding that is supported by other studies. 13 , 29 DIA can improve the reliability and reproducibility of grading in routine practice. 30 Thus, likely the pathology departments with this method or similar DIA available, can use DIA Ki67 as a part of their routine diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines established using histological samples have been extrapolated to grading PanNENs in cytology material (e.g., cell blocks) procured by FNA. Several studies have demonstrated that Ki-67 assessment by manual counting of tumor cells in cell blocks can result in under-grading of these neoplasms when compared with matched surgical resection specimens 36 , 42 , with discrepancies more often observed in G2 cases 20 , 29 . Intriguingly, Abi-Raad and colleagues demonstrated that counting hotspots instead of the complete cell block can provide a higher concordance with surgical specimens, especially for FNA samples that contain ≥ 1000 cells 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The assistance of artificial intelligence in digital image analysis has shown increased efficiency with comparable results to manual mitotic counts in breast cancer and melanoma 23‐25 . Artificial intelligence has been used in cell block material of gastric neuroendocrine tumours in the calculation of the Ki‐67 proliferation index 26,27 . However, there is no set risk stratification in GISTs for the use of the Ki‐67 proliferation index and artificial intelligence for mitotic counts has not yet been studied in either GISTs or cytology cell block material.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…[23][24][25] Artificial intelligence has been used in cell block material of gastric neuroendocrine tumours in the calculation of the Ki-67 proliferation index. 26,27 However, there is no set risk stratification in GISTs for the use of the Ki-67 proliferation index and artificial intelligence for mitotic counts has not yet been studied in either GISTs or cytology cell block material.…”
Section: Discussion/con Clus Ionmentioning
confidence: 99%